Colombian validation of the Family Functioning Scale in Crisis Situations (F-COPES) - Cabrera-García, Victoria Eugenia (2023)
The objective was to determine the psychometric properties of the F-COPES in the Colombian population. Cross-sectional study, with 1373 people, aged between 18 and 84 years. Data were analyzed in Jasp, exploratory factor analyzes were performed using the weighted least squares estimation method and a promax-type oblique rotation. Confirmatory factor analyzes with diagonalized weighted least squares estimators and robust analysis methods. Internal consistency analysis using Cronbach’s Alpha indices, McDonald’s Omega, and the highest lower limit index. A structure of five factors was found, four original ones: finding social support, cognitive restructuring, finding spiritual support and passive evaluation, and a new one: neighbor support. The scale evaluates family functioning in crisis situations in the Colombian context.